(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
New ruthenium (II) complexes, [Ru(DHZ)2(bpy)], [Ru(SCN)2(bpy)(DMSO)2], [Ru(SCN)2(dmbpy)(DMSO)2] and [RuCl2(salen)]-2, where bpy = 2,2’- bipyridine, DHZ = 1,5-diphenylthiocarbazone, dmbpy = 4,4’-dimethyl-2,2’ bipyridine and salen = 2,2’- ethylenebis(nitrilomethylidene)diphenol were synthesized and characterized by elemental analysis, FTIR, UV-Vis spectroscopy and thermal analysis. From data of these investigations the structural formula and the mode of bonding were obtained. These complexes were successfully applied to sensitization of nano-crystalline TiO2 based solar cells (DSSCs). The photovoltaic efficiencies of the studied DSSCs increase in the following order [Ru(DHZ)2(bpy)]< [Ru(SCN)2(bpy)(DMSO)2]< [Ru(SCN)2(dmbpy)(DMSO)2]< [RuCl2(salen)]-2. This increase is in agreement with the light harvesting of these complexes as indicated from their absorption spectra. Ferrioxalate complex enhanced the performance of some investigated cells. Therefore, a mechanism of this improvement has been postulated. Polyaniline as well as iodine doped polyaniline modified FTO electrode has been tested as promising counter electrodes. The efficiencies of the cells using iodine doped polyaniline is higher than that of polyaniline, which is assignable to the high conductivity of iodine.